IULIAN STĂNESCU, FLAVIUS MIHALACHE (eds.) „România rurală în noul capitalism”: 1990-2020”, Editura Pro Universitaria, București, 2022, 375 p. - Pop, Alina (Calitatea Vieții, 2022)
România rurală în noul capitalism [Rural Romania under the new capitalism], edited by Iulian Stănescu and Flavius Mihalache, is a collection of studies that address the multiple transformations affecting Romania’s rural areas in the three decades after the fall of communism. The “new capitalism” of contemporary Romania designates a new stage in the country’s social and economic development and is set in contrast with the old capitalism of the interwar period. The volume is divided into four sections that analyse different aspects of rural life, such as demography and legal status of rural municipalities, rural economy, quality of life, and social processes.